IMPLEMENTATION OF ISLAMIC RELIGIOUS EDUCATION LEARNING FOR DEAF CHILDREN AT SMALB - Ririn Ratna Winangsih; Rifa Nurfalah; Abdul Jamil; Afif Nurseha (Adisam Publisher, 2025)
Based on Law No. 20 of 2003 concerning the National Education System, Article 5 paragraph 2 states that citizens who have physical and mental disabilities have the right to receive special education, in this case deaf children. Islamic Religious Education is one of the religious subjects given in every formal education unit, one of which is in special high schools. This study aims to determine: 1) Islamic Religious Education learning planning at Kandaga Bina Bangsa Special High School, 2) Islamic Religious Education learning strategies at Kandaga Bina Bangsa Special High School, 3) Evaluation of Islamic Religious Education learning at Kandaga Bina Bangsa Special High School. The study used a qualitative approach with a descriptive type. The subjects of this study were 12 deaf students at Kandaga Bina Bangsa Special High School. Data collection techniques used interviews, observation, and documentation. The results of the study showed that 1) Islamic Religious Education learning planning at Kandaga Bina Bangsa Special High School is the same as schools in general, except that its preparation is adjusted to the conditions of the students, 2) The learning strategy uses an expository learning strategy with an individual learning method, Islamic Religious Education lesson time is given for 2 hours in one week, the media used is adjusted to the material, 3) Evaluation activities use types of tests, such as daily assessment results, mid-semester assessments, and end-of-semester assessment results.